2021
DOI: 10.3389/fpsyg.2021.689226
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Model Among Iranian Pre-Hospital Personnel in Disasters: A Grounded Theory Study

Abstract: Objective: Pre-hospital personnels (PHPs) who work in disasters under extreme pressure, uncertainty, and complex situations are victims of disasters themselves, and there is a link between experiencing such incidents and mental health problems. Because most studies focus on the injured and less on the psychological issues of PHPs, the present study aimed to develop a model to provide relief for PHPs in disasters from a psychological perspective.Methods: A grounded theory methodology recommended by Corbin and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The healthcare system refers to an organized group of individuals and resources that provide healthcare services to meet the needs of the target population [ 21 , 22 ]. The healthcare system aims to promote, restore, and maintain people’s health through the constant provision of healthcare services [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare system refers to an organized group of individuals and resources that provide healthcare services to meet the needs of the target population [ 21 , 22 ]. The healthcare system aims to promote, restore, and maintain people’s health through the constant provision of healthcare services [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Difficult situations encountered in patient care, such as cost recovery or non-recovery, and the inability to effectively cope with challenging situations like death can lead to feelings of powerlessness and professional dissatisfaction. [7][8][9] The World Health Organization emphasizes the importance of investing in prevention and improving the work environment's quality to protect workers' well-being and health. Recognizing other mental pathologies that may influence the development of burnout is also essential.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing other mental pathologies that may influence the development of burnout is also essential. [8][9][10] Factors such as distress symptoms, coping mechanisms, work limitations, job satisfaction, substance use for stress relief, alcohol consumption, and understanding of depression and anxiety should be considered when addressing burnout. 11 Prehospital emergency care is crucial in the health area, as it requires nurses to provide urgent and immediate care to individuals in emergencies outside the hospital context since SAMU ambulances are not always triggered by the presence of doctors in helping the victims.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, psychological injuries are often neglected and receive limited attention in disaster management plans. 8,9 Paying attention to psychological effects should be considered in all aspects of disaster management, including preparedness, mitigation, response, and recovery. 8,10 In this regard, nurses, as the largest group of health-care providers, are among the first responders in disasters.…”
mentioning
confidence: 99%
“…24,25 Therefore, it is very important to increase the competence of nurses in providing PFA during a disaster. 26 Competence consists of the dimensions of knowledge, skill, attitude, mission commitment, leadership, management ability self-identity of dual roles (such as obedience, empathy, etc), 27,28 critical thinking, innovation, and personality traits appropriate to the work field. 29 No study was found that investigated the level of competence of nurses in providing PFA.…”
mentioning
confidence: 99%